2017
DOI: 10.1002/ijc.31190
|View full text |Cite
|
Sign up to set email alerts
|

Polymethoxyflavones prevent benzo[a]pyrene/dextran sodium sulfate‐induced colorectal carcinogenesis through modulating xenobiotic metabolism and ameliorate autophagic defect in ICR mice

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are widespread environmental carcinogenic pollutants and they have become an important issue in food contamination. Dietary intake of PAHs has been recognized as a major route of human exposure. However, the mechanisms behind dietary PAH-induced colorectal cancer (CRC) remain unclear. Several studies have shown that polymethoxyflavones (PMFs) are effective in preventing carcinogen-induced CRC or colitis. In this study, we investigated the preventive effect of PMFs on ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…Similarly, in cellular companion (CC) module, there were 4 terms relative to molecular binding. Some reports found that retinoid acid binding receptor inhibited cancer cell apoptosis by regulating miR-22/NUR77 axis (21,22). Interestingly, from the results of KEGG pathway enrichment analysis, we found that the genes mainly enriched in molecular metabolism, being consistent with BP of GO enrichment, and the drug, retinoid and porphyrin metabolism are proved involving in irregulated tumor cell metabolism, and resulted in chemotherapy resistant (23).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Similarly, in cellular companion (CC) module, there were 4 terms relative to molecular binding. Some reports found that retinoid acid binding receptor inhibited cancer cell apoptosis by regulating miR-22/NUR77 axis (21,22). Interestingly, from the results of KEGG pathway enrichment analysis, we found that the genes mainly enriched in molecular metabolism, being consistent with BP of GO enrichment, and the drug, retinoid and porphyrin metabolism are proved involving in irregulated tumor cell metabolism, and resulted in chemotherapy resistant (23).…”
Section: Discussionsupporting
confidence: 66%
“…A lot of reports show that retinoic acid metabolic process associates with colonic tumorigenesis and metastasis, such as retinoic acid metabolizing enzymes CYP26B1, LRAT and CYP26A1 over expressed in colorectal cancer tissues and that LRAT and CYP26B1 signi cantly associated with the prognosis of the colorectal cancers (19). Xenobiotic metabolic process also involves in the carcinogenesis and development of cancer, because colonic epithelium is exposed to various compounds from diet, and the compounds can be metabolized to the procarcinogens, which are the risks of colonic cancer (20,21). Similarly, in cellular companion (CC) module, there were 4 terms relative to molecular binding.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first report on the comprehensive analysis of the mechanism of the antitumor action of butyric acid, isobutyric acid, and acetic acid in human colon cancer cells. The Wnt/β-catenin, PI3K/Akt/mTOR and Ras/MEK/ERK signalling systems are known as oncogenic pathways of colorectal cancer (17)(18)(19). The analysis revealed that the main mechanism of the antitumor activity of SCFAs was suppression of tumour growth and metabolic functions such as cell cycle, DNA replication, recombination and repair, and almost no suppression of cancer-related genes.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports found that retinoid acid binding receptor inhibited cancer cell apoptosis by regulating the miR-22/ NUR77 axis. 25,26 From the results of KEGG pathway enrichment analysis, we found that the genes were mainly enriched in molecular metabolism, and drug, retinoid and For personal use only.…”
Section: Dovepressmentioning
confidence: 99%